Inventory Control Analysis of Plastic Raw Materials Using Monte Carlo Simulation Approach - Lusi Mei Cahya Wulandari; Laurensia Dilawati Indrianto Putri (OPSI, 2021)
Excess inventory of goods is one factor in increasing production costs and can reduce the profits earned by the company. The company's ability to control the supply of raw materials is the key to the continuity of the production process. This study aims to determine an inventory method that minimizes the cost of supplies of plastic pellets using the Economic Order Quantity (EOQ), Economic Order Interval (EOI), and Min-Max methods. A Monte Carlo simulation approach with Perpetual Simulation, Periodic Simulation, and Min-Max Simulation can use determine the appropriate inventory method in the future. Based on current demand, the EOQ method produces the lowest total cost of inventory. Meanwhile, through a simulation by predicting demand in the next 34 months, the EOQ method also affords the lowest total cost of inventory.